A face amável do Deus terrível: uma hermenêutica do confronto a partir do imaginário bíblico - Lima, Eduardo Sales de (2013)
That work has, for objective, to recognize the structures that use the imaginary divine to legitimate the perpetuation of the power. For that understanding it was used the modern philological historiografic hermeneutics, sensitive to the structures and ideological manipulations. Philology, according to Bakhtin and Benveniste, and historiography to the school of Annáles. Of ownership of those perspectives hermeneutics, it was possible to move forward towards the imaginary biblical. The Bible was understood as a control instrument used to legitimate the structures of power of the old world. In that research, the imaginary of the old world was represented as a kind of global theology, in that the imaginary of a Terrible God was used, in the nations of the Fertile Crescent, to legitimate the dominance and the perpetuation of the power. Finally, leaning in the dialogical hermeneutics , it was possible to confront the imaginary of Terrible God with Kind God. The writing of the second testament follows the texts of resistance of the Hebraic Bible and they reveal a dialogical dimension. Kind God is an answer to Terrible God preached by the dominant ideology. That reflection allowed the re-read of several confrontation texts for recovery of the meaning. That research is relevant for the pastoral practice, because the community's reading of the Bible still didn't notice the ideological manipulations in that the text was produced.